Lessons learned from a prolonged and costly norovirus outbreak at a Scottish medicine of the elderly hospital: case study. Issue 2 (June 2016) - Danial, J.; Ballard-Smith, S.; Horsburgh, C.; Crombie, C.; Ovens, A.; Templeton, K.E.; Hardie, A.; Cameron, F.; Harvey, L.; Stevenson, J.; Johannessen, I.
Summary: Background: Norovirus outbreaks are a major burden for healthcare facilities globally. Aim: Lessons learned to inform an action plan to improve facilities as well as responses to norovirus within the medicine of the elderly (MoE) hospital as well as other NHS (National Health Service) Lothian facilities. Methods: This study investigated the impact of a prolonged outbreak at an MoE hospital in one of the 14 Scottish health boards between February and March 2013. Findings: In all, 143 patients (14.80 cases per 1000 inpatient bed-days) and 30 healthcare staff (3.10 cases per 1000 inpatient bed-days) were affected clinically and 63 patients were confirmed virologically. Restricting new admissions to affected units resulted in 1192 lost bed-days. The cost due to lost bed-days in addition to staff absence and management of the outbreak was estimated at £341, 534 for this incident alone. At certain points during the outbreak, the whole facility was closed with resulting major impact on the health board's acute care hospitals. Conclusion: Due to the outbreak, new measures were implemented for the first time within NHS Lothian that included floor-by-floor (instead of individual) ward closures, enhanced cleaning with chlorine-based products throughout the hospital, reduction in bed capacity with enhanced bed-spacing and interruption to direct admissions from the Board's general practice surgeries, and temporary suspension of visitors to affected areas. Together with regular communication to staff, patients, relatives, and the public throughout the outbreak and good engagement of staff groups in management of the incident, the outbreak was gradually brought under control.